2021
DOI: 10.1007/s10869-021-09779-8
|View full text |Cite
|
Sign up to set email alerts
|

The General Factor of Personality (GFP) and Vocational Interests: a Test of Social Effectiveness at the Behavioral and Genetic Level

Abstract: Previous studies have examined how personality models (e.g., Big Five, HEXACO) relate to vocational interests. We adopt a novel approach by testing the associations between personality and vocational interests from the perspective of the general factor of personality (GFP). One interpretation of the GFP is that it reflects social effectiveness. Based on this interpretation, we predicted that the GFP is particularly related to interest in social jobs because people generally tend to be attracted to activities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…In contrast to the lower‐order trait models, the existence of the highest‐order personality trait model (the GFP) is trying to find the core variables that influence individual behaviors (Zhu & Yan, 2015). Much evidence has revealed the predictive effect of the GFP in various social domains, including individuals' interpersonal relationship quality (Pelt et al, 2020), quality of life and well‐being (Musek, 2017), vocational interests (Van der Linden et al, 2022), future criminal behavior (Watters et al, 2020), and moral values (Kawamoto et al, 2017). Therefore, it is possible that the GFP may also predict moral hypocrisy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the lower‐order trait models, the existence of the highest‐order personality trait model (the GFP) is trying to find the core variables that influence individual behaviors (Zhu & Yan, 2015). Much evidence has revealed the predictive effect of the GFP in various social domains, including individuals' interpersonal relationship quality (Pelt et al, 2020), quality of life and well‐being (Musek, 2017), vocational interests (Van der Linden et al, 2022), future criminal behavior (Watters et al, 2020), and moral values (Kawamoto et al, 2017). Therefore, it is possible that the GFP may also predict moral hypocrisy.…”
Section: Introductionmentioning
confidence: 99%
“…Although existing research has found evidence that the Big Five personality traits are related to certain unethical behaviors (Hart et al, 2020; Koodamara et al, 2020), the relationship between personality traits (the Big Five) and moral hypocrisy has not been tested directly. In addition, a growing body of research has found a relatively high correlation between the Big Five personality traits in general (Van der Linden et al, 2022; Musek, 2017; Pelt et al, 2020; Wu et al, 2022). The emergence of the GFP implies that the highest‐order factors reflect the general level of the Big Five personality traits (Zhu & Yan, 2015) and might fit the correlations better among the five traits (Musek, 2017).…”
Section: Introductionmentioning
confidence: 99%